2018
DOI: 10.1103/physrevc.98.064607
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the tensor force on the microscopic heavy-ion interaction potential

Abstract: Background: The tensor interaction is known to play an important role in the nuclear structure studies of exotic nuclei. However, most microscopic studies of low-energy nuclear reactions neglect the tensor force, resulting in a lack of knowledge concerning the effect of the tensor force on heavy-ion collisions. An accurate description of the heavy-ion interaction potential is crucial for understanding the microscopic mechanisms of heavy-ion fusion dynamics. Furthermore, the building blocks of the heavy-ion int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 87 publications
(128 reference statements)
0
24
0
Order By: Relevance
“…The effects of these terms on heavy-ion fusion have been recently studied [64][65][66]. However, a comparison of the nucleus-nucleus potentials calculated with the SLy5 functional (without tensor) [67] and with SLy5t (including tensor) [68] showed that the effect is quite small for 12 C+ 12 C [69].…”
Section: Energy-density Functionalmentioning
confidence: 99%
“…The effects of these terms on heavy-ion fusion have been recently studied [64][65][66]. However, a comparison of the nucleus-nucleus potentials calculated with the SLy5 functional (without tensor) [67] and with SLy5t (including tensor) [68] showed that the effect is quite small for 12 C+ 12 C [69].…”
Section: Energy-density Functionalmentioning
confidence: 99%
“…For details in the energy functional, see Refs. [42,43,51]. This force has been widely used in the fully three-dimensional TDHF calculations in heavy-ion collisions [34][35][36]42,43,[49][50][51]56,57,[59][60][61].…”
Section: Resultsmentioning
confidence: 99%
“…Quantum effects such as the Pauli principle and antisymmetrization of wave functions are also automatically taken into account in TDHF, which are essential for the manifestation of shell structures during the collision dynamics. TDHF approach has many successful applications in the description of nuclear large amplitude collective motions, as seen in recent applications to fusion [36][37][38][39][40][41][42][43], quasifission [44][45][46][47][48][49][50][51][52], transfer reactions [49,[53][54][55][56][57][58][59][60][61][62][63], fission [64][65][66][67][68], and deep inelastic collisions [69][70][71][72][73][74][75][76][77][78]. However, since the dynamical fluctuation and two-body dissipation are not included in TDHF, the fluctuations of collective variables are found to be considerably underestimated [79,…”
Section: Introductionmentioning
confidence: 99%
“…TDHF calculations may be used to compute the ratio of fusion cross sections to capture cross sections. In addition, the TDHF method may be used to explore the effect of the orientation of the projectile and the target at the contact point, and the role of the nuclear shell structure and tensor force [104][105][106][107][108][109][110][111][112][113][114][115].…”
Section: Fusion Dynamicsmentioning
confidence: 99%